2020
DOI: 10.3390/ijms21030947
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutation as a Potential Predictive Biomarker in BCG-Treated Bladder Cancer Patients

Abstract: Telomerase reverse transcriptase gene promoter (TERTp) mutations are recognized as one of the most frequent genetic events in bladder cancer (BC). No studies have focused on the relevance of TERTp mutations in the specific group of tumors treated with Bacillus Calmette–Guérin (BCG) intravesical therapy. Methods — 125 non muscle invasive BC treated with BCG therapy (BCG-NMIBC) were screened for TERTp mutations, TERT rs2853669 single nucleotide polymorphism, and Fibroblast Growth Factor Receptor 3 (FGFR3) hotspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
(66 reference statements)
4
17
0
Order By: Relevance
“…TERT mutations are also outlined as markers of tumor aggressiveness and poor prognosis in several human cancer types 24‐28 . A recent study revealed that in bladder cancer, TERT promoter mutation appeared to be a potential predictive marker of response to Bacillus Calmette‐Guérin treatment which was regarded as one of the first and most successful oncological immunotherapy 29 . Therefore, TERT mutations may be used as a predictive marker for ICI responses.…”
Section: Introductionmentioning
confidence: 99%
“…TERT mutations are also outlined as markers of tumor aggressiveness and poor prognosis in several human cancer types 24‐28 . A recent study revealed that in bladder cancer, TERT promoter mutation appeared to be a potential predictive marker of response to Bacillus Calmette‐Guérin treatment which was regarded as one of the first and most successful oncological immunotherapy 29 . Therefore, TERT mutations may be used as a predictive marker for ICI responses.…”
Section: Introductionmentioning
confidence: 99%
“…TERTp mutation has not been reported as a prognostic factor in cBCCs [14][15][16] , at variance with other skin cancers, such as squamous cell carcinoma 41 and melanoma 18,33 in which TERTp mutations were associated with an ominous outcome. Contrarily, in the bladder cancer model, the − 146:G > A was an independent predictor of nonrecurrence after BCG therapy in the BCG-NMI tumors 42 .…”
Section: Discussionmentioning
confidence: 91%
“…Mutations in the core promoter region of TERT cause telomerase reactivation in 60-80% of urothelial bladder tumors 13 . The TERT C228T mutation has been shown to be significantly associated with the prognosis of bladder cancer, particularly with bladder recurrence in NMIBC 14 , whereas TERT C250 mutation appears to be an independent predictive marker of response to BCG treatment 15 . However, in our series, neither C228T nor C250 mutation was associated with prognosis of NMIBC or response to BCG-therapy.…”
Section: Discussionmentioning
confidence: 98%